Psychological Reactions in Women with Pregnancy Termination Due to Fetal Anomaly - Gurcan Turkyilmaz; Yavuz Selim Atan; Emircan Erturk; Sebnem Turkyilmaz (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: We aimed to determine and compare grief, depression, and post-traumatic stress scores in women who underwent termination of pregnancy due to fetal anomaly in the first vs. second-trimester of pregnancy.